Training program on “Strengthening Anticipatory Action and Early Warning through the AWARE Platform” in Sri Lanka - Alahacoon, Niranga; Amarnath, Giriraj; Dickowita, Ranoja (International Water Management Institute, 2025)
The national training program on “Strengthening Anticipatory Action and Early Warning through the AWARE Platform” brought together staff from the Disaster Management Centre (DMC) and technical agencies to enhance skills in proactive, forecast-based disaster Risk Management. As climate extremes intensify across Sri Lanka, ranging from prolonged droughts to flash floods, the need for timely, data-driven early warning systems has become critical. The AWARE Platform, developed by IWMI with key partners, serves as a digital decision-support tool that integrates climate and hydrological forecasts and real-time monitoring. The workshop opened with remarks emphasizing the importance of shifting from reactive response to anticipatory action, supported by national institutions such as the Department of Meteorology, NBRO, and the Irrigation Department. Participants were introduced to AWARE’s three core pillars: Early Warning, Early Action, and Early Finance, and explored how the system brings together multi-source data to trigger timely, evidence-based preparedness measures. A hands-on session guided participants through forecast interpretation, alert dashboards, rapid-response flood mapping, and digitized early action protocols. Discussions highlighted the need for improved data validation, sector-specific triggers, district-level data entry, and stronger inter-agency integration. The program concluded with appreciation from DMC leadership and a shared commitment to operationalizing AWARE ahead of the 2025 monsoon season.